The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1523/jneurosci.1674-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

MuSK Expressed in the Brain Mediates Cholinergic Responses, Synaptic Plasticity, and Memory Formation

Abstract: Muscle-specific tyrosine kinase receptor (MuSK) has been believed to be mainly expressed and functional in muscle, in which it mediates the formation of neuromuscular junctions. Here we show that MuSK is expressed in the brain, particularly in neurons, as well as in non-neuronal tissues. We also provide evidence that MuSK expression in the hippocampus is required for memory consolidation, because temporally restricted knockdown after training impairs memory retention. Hippocampal disruption of MuSK also preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 74 publications
5
81
2
1
Order By: Relevance
“…1A). An unpaired (UP) control group was exposed to the IA context and received the footshock, but these two experiences were separated by 1 h and were therefore unpaired, preventing IA learning (Garcia-Osta et al 2006). Immunoblot analysis using MMP-9-specific antisera that recognize both proand active-forms shows that IA training induces a gradual and transient increase in levels of both forms of MMP-9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). An unpaired (UP) control group was exposed to the IA context and received the footshock, but these two experiences were separated by 1 h and were therefore unpaired, preventing IA learning (Garcia-Osta et al 2006). Immunoblot analysis using MMP-9-specific antisera that recognize both proand active-forms shows that IA training induces a gradual and transient increase in levels of both forms of MMP-9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Animals were returned to their home cages for 1 h, then brought back and footshocked directly (2 sec, 0.65 mA), without further exploration. Previous studies have shown that such UP controls fail to form IA memory or display IA training-induced changes in expression of certain genes (Garcia-Osta et al 2006). After footshock, UP control rats were returned to their home cages and were sacrificed at 24 or 48 h post-shock.…”
Section: Inhibitory Avoidance Taskmentioning
confidence: 99%
“…Using Northern blot analysis, MuSK is not detected in rat brain (Valenzuela et al, 1995). In contrast, transcripts for MuSK were found in the brain of other species (Ganju et al, 1995;Fu et al, 1999;Garcia-Osta et al, 2006). Because agrin signaling in the brain might be mediated by MuSK, we looked at the expression of MuSK on the mRNA and protein level.…”
Section: The Receptor Tyrosine Kinase Musk Is Localized To Cns Synapsesmentioning
confidence: 94%
“…No effects were observed with the presentation of scrambled OGNs to either type of neuron. In another study (Garcia-Osta et al, 2006), intracerebral delivery of antisense OGN for a brain-expressed and muscle-specific tyrosine kinase receptor (MuSK) disrupted the ability of the local hippocampal network to generate theta activity in vitro. These results suggest that specific protein products of a neuron are a vital part of its ability to function on its own and within a network; inhibiting just one product can have devastating effects on electrical activity and responsiveness.…”
Section: Is Protein Synthesis Necessary For Neural Activity?mentioning
confidence: 99%